Synthesis and Characterization of Thermosensitive Poly(organophosphazene) Gels with an Amino Functional Group - Lee, Bae Boon; Song, Soo-Chang (WILEY, 2011)
Thermosensitive poly(organophosphazene) gels have been synthesized with a host of side groups, including alpha-amino-omega-methoxy-poly(ethylene glycol), hydrophobic amino acid esters (PheOEt, LeuOEt, and IleuOEt), depsipeptide ethyl ester (GlyGlycOEt), and lysine ethyl ester (lysOEt). The fraction of the last side group, lysOEt, which possesses two amine functional groups, was designed to be in the range of 0.1-0.3 mol per polymer unit. The poly(organophosphazenes) have been characterized via H-1- and P-31-NMR spectroscopies, GPC, and elemental analysis. The phase transition behavior of the poly(organophosphazenes) in aqueous solution has been determined via viscometry. Some of the poly(organophosphazenes) with amino functional groups exhibit reversible sol gel transitions at temperatures near those of the human body, when in aqueous solution. These polymers form a sol at lower temperatures, and become gels at higher temperatures. Also, these polymer solutions have been found to behave generally like Newtonian fluids in the sol state, but appear to exhibit pseudoplastic qualities in the gel state. The polymers possessing depsipeptide ethyl esters (ethyl-2-(O-glycyl)glycolate) as a side group tend to exhibit much higher degradation rates under physiological conditions than do those which lack the depsipeptide ethyl ester group. 0 (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 998-1005, 2011
Keywords: AQUEOUS-SOLUTIONS; COPOLYMERS; DELIVERY; RELEASE